Предмет: Математика, автор: IpurpleYouTaeh

19 баллов
-1/20+2/30-3/20+4/30

Ответы

Автор ответа: Аноним
0

 -  \frac{1}{20}  +  \frac{2}{30}  -  \frac{3}{20}  +  \frac{4}{30}  = ( -  \frac{1}{20}  -  \frac{3}{20} ) + ( \frac{2}{30}  +  \frac{4}{30} ) =  -  \frac{4}{20}  +  \frac{6}{30}  =  -  \frac{1}{5}  +  \frac{1}{5}  = 0

Автор ответа: Аноним
0

\displaystyle -\frac{1}{20}+\frac{2}{30}-\frac{3}{20}+\frac{4}{30}=\frac{-1-3}{20}+\frac{2+4}{30}=\frac{-4}{20}+\frac{6}{30}=-\frac{1}{5}+\frac{1}{5}=0

Похожие вопросы